Book Auction Mobile Application (BAcMAp) for UiTM Jasin community / Noor Fazira Amir - Amir, Noor Fazira (Faculty of Computer and Mathematical Sciences, 2017)
Book is the main resource for all people since the ancient time. In UiTM Jasin and other University, students are quit reluctant in buying new books as for its high price and sometimes the books are out of stock early in the semesters, they preferred to buy books from seniors. The current way of doing the book selling is by using social media as the platform. The book's information given is insufficient and finding the right seller takes a lot of time. The motivation that drives to the construction of this project is to develop an application that will handle the process of book trading in UiTM Jasin. Moreover, it has been found out during the survey that there are no system yet to be developed to assist the process. The significant of this project would be to help the student in finding books for more orderly manner rather than manually search. Auction is one of the method for business and commerce and will be used in this system. An auction is the point at which a property is sold at a particular time and place to the most noteworthy bidder. Using mobile application for an auction will make the auction process more efficient and convenient for student. The methodology used to assist this project is Mobile Application Development Life Cycle (MADLC) that consists of identification phase, design phase and development phase. The proposed app which called BAcMAp will keep student or buyers updated with the latest available books and bidding price update in real time, it will also provide a platform for seniors or sellers to swiftly sell their unused books to the interested buyers. This work can be further extended to enhance the functionality and features to improve user experience and make it more acceptable for the user.